Consumer Consciousness and Motivational Factors in Second-Hand Clothing Purchases: A Systematic Literature Review - Bence Végvári; Virág Walter; Gábor Szabó-Szentgróti (Decision Making: Applications in Management and Engineering, 2025)
The fast fashion industry poses significant environmental challenges, which have driven a growing number of consumers to adopt more sustainable shopping habits. Alongside environmental concerns, rising consumer prices have accelerated the growth of the second-hand clothing market. The study aims to provide a theoretical foundation for research on consumer motivations in the second-hand clothing market. By systematically reviewing recent international literature, the study identifies key factors, dimensions, and measurement tools used to understand consumer behavior in this domain. A systematic literature review was conducted using articles from the Scopus and Web of Science databases, focusing on publications from the last 10 years. Strict exclusion criteria were applied to ensure the relevance and quality of the analyzed works. Purchasing second-hand clothing reduces waste, minimizes the demand for new clothing production, and decreases resource use and pollution. Motivational factors include the "treasure hunting" aspect of second-hand shopping and its environmental benefits. Businesses can capitalize on these motivations to engage environmentally conscious consumers. Businesses should emphasize the treasure-hunting experience of second-hand shopping alongside the environmental benefits, which could potentially reach the growing share of environmentally conscious consumers. Policymakers should adopt practices for sustainable consumption behavior, such as second-hand clothing purchases with reduced taxation, encouraging environmentally friendly consumer behavior